PROTOCOL: Government‐Led Communication Campaigns for Reducing Violent Extremism − A Systematic Review - Ghayda Hassan; Sébastien Brouillette‐Alarie; Kurt Braddock; Sarah Carthy; Wynnpaul Varela; Pablo Madriaza; Paul Gill (Campbell Systematic Reviews)
ABSTRACT This is the protocol for a Campbell systematic review. The main objective of this project is to gather, critically appraise, and synthesize evidence about the effectiveness of government‐led communication campaigns geared toward preventing violent extremism.